1997
DOI: 10.1128/jb.179.20.6285-6293.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of alpha-acetolactate decarboxylase in Lactococcus lactis subsp. lactis

Abstract: The ␣-acetolactate decarboxylase gene aldB is clustered with the genes for the branched-chain amino acids (BCAA) in Lactococcus lactis subsp. lactis. It can be transcribed with BCAA genes under isoleucine regulation or independently of BCAA synthesis under the control of its own promoter. The product of aldB is responsible for leucine sensibility under valine starvation. In the presence of more than 10 M leucine, the ␣-acetolactate produced by the biosynthetic acetohydroxy acid synthase IlvBN is transformed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 53 publications
4
70
0
1
Order By: Relevance
“…Since the CodY signal in L. lactis is essentially mediated by isoleucine, excess of this amino acid in the environment leads to growth inhibition by blocking inappropriately CodY-dependent biosynthesis pathways. Several studies in chemically defined media have reported a CodY-dependent isoleucine growth inihibition in L. lactis linked to repression of the biosynthesis of valine and leucine (Goupil-Feuillerat et al, 1997), asparagine, histidine, lysine and threonine (this work) and glutamate (Lapujade et al, 1998). In the latter case, the growth defect was shown to be the result of a reduced synthesis of 2-oxoglutarate associated with a low level of the glutamate synthase (Lapujade et al, 1998).…”
Section: Isoleucine Signal and Nitrogen Metabolismmentioning
confidence: 69%
“…Since the CodY signal in L. lactis is essentially mediated by isoleucine, excess of this amino acid in the environment leads to growth inhibition by blocking inappropriately CodY-dependent biosynthesis pathways. Several studies in chemically defined media have reported a CodY-dependent isoleucine growth inihibition in L. lactis linked to repression of the biosynthesis of valine and leucine (Goupil-Feuillerat et al, 1997), asparagine, histidine, lysine and threonine (this work) and glutamate (Lapujade et al, 1998). In the latter case, the growth defect was shown to be the result of a reduced synthesis of 2-oxoglutarate associated with a low level of the glutamate synthase (Lapujade et al, 1998).…”
Section: Isoleucine Signal and Nitrogen Metabolismmentioning
confidence: 69%
“…As we show that this operon is one of major targets of CodY (TABLE THREE) and CodYboxes are present in its upstream and coding regions (TABLE FOUR), CodY most probably directly controls ilv expression. Moreover, repression of this operon has been shown to be dependent on the BCAA Ile (51)(52)(53), which is the most potent modulator of CodY activity, as it has been shown that CodY binding to the promoter region of at least one of its targets, oppD, in DNA binding studies is stimulated most by this particular BCAA (17).…”
Section: Discussionmentioning
confidence: 99%
“…A different group of genes, the transcription of which was found to be elevated in L. lactis MG1363⌬codY, encompasses those involved in BCAA metabolism; the ilv-ald operon for BCAA biosynthesis (51,52) was derepressed over five times. Thus, although L. lactis MG1363 like many other lactococcal dairy strains is auxotrophic for these amino acids, several genes of the BCAA biosynthetic operon are present on the chromosome and are actively transcribed (1,53).…”
Section: Role Of Cody In Global Genementioning
confidence: 99%
“…Such strains are widely used in butter-making processes (Veringa et al, 1976) and for 58 the production of aroma additives with a high -acetolactate (Kuiper et al, 1987) or diacetyl 59 (Jönsson et al, 1980) content. In Lactococcus lactis strains isolated from non-dairy 60 environments, -acetolactate decarboxylase is also involved in the regulation of leucine and 61 valine biosynthesis (Goupil-Feuillerat et al, 1997). Indeed, -acetolactate is a precursor of 62 these branched-chain amino acids, and when they are present in excess, the flux of -63 acetolactate is diverted towards acetoin, due to an allosteric activation of the -acetolactate 64 decarboxylase (Phalip et al, 1994) and to a translational regulation of -acetolactate g/l), L-aspartate (300 mg/l) and L-tyrosine (100 mg/l).…”
mentioning
confidence: 99%